2020
DOI: 10.1242/dev.185629
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes occur at decidualisation genes as a function of reproductive ageing in mice

Abstract: Reproductive decline in older female mice can be attributed to a failure of the uterus to decidualise in response to steroid hormones. Here, we show that normal decidualisation is associated with significant epigenetic changes. Notably, we identify a cohort of differentially methylated regions (DMRs), most of which gain DNA methylation between the early and late stages of decidualisation. These DMRs are enriched at progesterone-responsive gene loci that are essential for reproductive function. In female mice n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Gene profiling has determined that pre-menopausal and peri-menopausal eMSC exhibit similar transcriptomic signatures, although in the same study, endometrial stromal fibroblasts from these two groups showed altered pathway activation [54]. Possibly of relevance here is that in a non-menstruating species, the laboratory mouse, there are major maternal-age associated problems of stromal decidualization, which interfere with subsequent placental development [55]. Most recently Devesa-Peiro et al [56] unsupervised artificial intelligence methods to raw data from previously published transcriptomic studies and analysed normal endometrium from women of different ages with regular menstrual cycles using algorithms that defined age groups.…”
Section: Effects Of Ageingmentioning
confidence: 73%
“…Gene profiling has determined that pre-menopausal and peri-menopausal eMSC exhibit similar transcriptomic signatures, although in the same study, endometrial stromal fibroblasts from these two groups showed altered pathway activation [54]. Possibly of relevance here is that in a non-menstruating species, the laboratory mouse, there are major maternal-age associated problems of stromal decidualization, which interfere with subsequent placental development [55]. Most recently Devesa-Peiro et al [56] unsupervised artificial intelligence methods to raw data from previously published transcriptomic studies and analysed normal endometrium from women of different ages with regular menstrual cycles using algorithms that defined age groups.…”
Section: Effects Of Ageingmentioning
confidence: 73%
“…It remains unclear whether the endometrium ages across the reproductive lifespan in humans 159,160 . However, in mice, a blunted steroid hormonal response and reduced DNA methylation leads to defects in the decidualization phase with ageing which, in turn, negatively impacts reproductive outcomes 161,162 .…”
Section: Factors Affecting Aubmentioning
confidence: 99%
“…TET1, TET2, and TET3, which constitute a family of iron (II)/2-oxoglutarate-dependent dioxygenase, are responsible for catalyzing the conversion of 5mC to 5-hydroxymethylcyosine (5hmC), 5-formylytosine (5fC), and 5-carboxylcyosine (5caC) to achieve the DNA demethylation process ( 24 26 ). These enzymes are associated with several conserved signaling pathways in several kinds of organs or tissues during development, especially in embryo and cancer development ( 27 , 28 ).…”
Section: Common Features Of Tet Proteinsmentioning
confidence: 99%